Built Lens: Designing Environmental Engagement on Flathead Lake - Eddy, Sarah Kathleen (My University, 2014)
This thesis explores the capacity of the built environment to serve as a lens in mediating man's relationship with the relatively un-built environment at a site located on Flathead Lake. Our presence on Flathead Lake in northwestern Montana is a paradoxical one. Power generation, recreational activity resulting in development on the lake and rich farmland in the Flathead Valley have changed, and will continue to change, the form and appearance of the landscape. The desire to conserve is met with the realization that the lake's intrigue is born from human interaction with it. Those who have visited share a collective memory of a powerful place: a place deserving ritual designed to provoke the critical double awareness of joy and shame man should feel when realizing human impact on the environment. With an interpretive facility, trails, and landscape interventions, this thesis seeks to reduce the distance between visitors and the lake through architecturally choreographed immersive experience.
Thesis (Master's)--University of Washington, 2013
Keywords: Flathead Lake; interpretive center; Architecture; architecture